INFLUENCE OF COLLOID-CHEMICAL STATE OF HEAVY METALS IONS ON MORPHOLOGY AND PHASE COMPOSITION OF THEIR OXIDE FORMS (COMPOUNDS Co and Cd) - A. S. Panasugin; D. P. Mihalap; V. L. Tribushevski; S. L. Rimoshevski; D. E. Ivanov (Литьë и металлургия, 2006)
The speed of β-Cd(ОН)2 dehydration is studied. It is shown that at 300 °C and higher β –Cd(OH)2 dehydration with forming of the product of composition CdO0,8 occurs